1971
DOI: 10.1113/jphysiol.1971.sp009407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ouabain and metabolic inhibitors on the Na and K movements of nucleotide contents of L cells

Abstract: SUMMARY1. The general characteristics and Na and K movements of L cells (derived from mouse epithelium) have been measured. Both cells grown in suspension (LS cells) and as a monolayer (L cells) were used.2. The volume of L cells was 1-2 x 10-9 cm3 and of LS cells 3-5 x 10-9 cm3; of this 82 % was water.3. Electron micrographs showed the presence of numerous protrusions (filopodia) from both forms of the cell. These had the effect of increasing the surface area of the cell by 2-4 times over smooth cells of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1971
1971
1983
1983

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…The results ( Table 2) show clearly that trypsin or bringing the cells into suspension has no effect on ouabain uptake, although the apparent surface area of cells in suspension is only half of that in a monolayer. In previous work (Lamb & MacKinnon, 1971) it was shown that the surface area of L cells (as measured by the electronmicroscope) in these two conditions was constant and adjustments for cell size were made by alteration of the number of filopodia protruding from the surface membrane. The present results are clearly in agreement with this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…The results ( Table 2) show clearly that trypsin or bringing the cells into suspension has no effect on ouabain uptake, although the apparent surface area of cells in suspension is only half of that in a monolayer. In previous work (Lamb & MacKinnon, 1971) it was shown that the surface area of L cells (as measured by the electronmicroscope) in these two conditions was constant and adjustments for cell size were made by alteration of the number of filopodia protruding from the surface membrane. The present results are clearly in agreement with this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…(1) The chloride contents and fluxes were measured, using 36C1 in a technique identical to that described for 24Na and 42K in the last paper (Lamb & MacKinnon, 1971) and (2) the membrane potentials of the cells were measured, using conventional micro-electrodes. Cells were cultured on plastic Petri dishes, using methods similar to those described in the last paper.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows the mean volume, surface area and V/A ratio of the cells used. The figures shown for surface area do not take account of any 'filopodia' present on the cell surface (Lamb & MacKinnon, 1971a), but do assume that both surfaces of the cells on the monolayer were available for ion transfer (Burrows & Lamb, 1962). As in previous work it was found that trypsinization did not alter the volume of the cells.…”
Section: Solutions Usedmentioning
confidence: 99%